2011
DOI: 10.1007/s11689-011-9092-5
|View full text |Cite
|
Sign up to set email alerts
|

Prader–Willi syndrome and autism spectrum disorders: an evolving story

Abstract: Prader–Willi syndrome (PWS) is well-known for its genetic and phenotypic complexities. Caused by a lack of paternally derived imprinted material on chromosome 15q11–q13, individuals with PWS have mild to moderate intellectual disabilities, repetitive and compulsive behaviors, skin picking, tantrums, irritability, hyperphagia, and increased risks of obesity. Many individuals also have co-occurring autism spectrum disorders (ASDs), psychosis, and mood disorders. Although the PWS 15q11–q13 region confers risks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 97 publications
2
80
0
1
Order By: Relevance
“…As the individual enters early childhood, the failure to thrive is replaced by hyperphagia (excessive eating) that results in severe obesity [44]. In addition, these individuals have a distinct behavioral phenotype characterized by repetitive and stereotyped behaviors; up to 35 % of them receive a diagnosis of ASD [45]. The association with 15q11.2-13.1 was identified through high-resolution karyotype analysis [46] and the RNA processing gene SNURF-SNRPN or proximal small nucleolar RNAs (snoRNAs) are implicated in many symptoms [47].…”
Section: Q112-131: Syndromes That Vary With Imprintingmentioning
confidence: 99%
“…As the individual enters early childhood, the failure to thrive is replaced by hyperphagia (excessive eating) that results in severe obesity [44]. In addition, these individuals have a distinct behavioral phenotype characterized by repetitive and stereotyped behaviors; up to 35 % of them receive a diagnosis of ASD [45]. The association with 15q11.2-13.1 was identified through high-resolution karyotype analysis [46] and the RNA processing gene SNURF-SNRPN or proximal small nucleolar RNAs (snoRNAs) are implicated in many symptoms [47].…”
Section: Q112-131: Syndromes That Vary With Imprintingmentioning
confidence: 99%
“…Furthermore, the relationship between intelligence, age, and EF is unclear and none of the studies completed to date have reported on subtype difference in EF abilities among children with PWS. Lastly, research is emerging on the common characteristics between PWS and autism (Dykens, Lee & Roof, 2011), but comparisons on EF have yet to be completed between PWS and other clinical groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, congenital abnormalities are often observed, including hypogonadism, facial dysmorphism, and small hands and feet, among others. PWS can also be associated with psychosis, mood disorders, and ASD [61].…”
Section: Prader-willi and Angelman Syndromesmentioning
confidence: 99%